Rehabilitation in the Intensive Care Unit - Yahya Ali Hussain Al Abood; Maryam Ali Nasser Alabbad; Fatimah Ibrahim Hejji Alsenawi; Zainab Ali H Alruhaish; Hawra Yousuf Ali Aljamaan; Anwer Towfiq Albaqshi; Mohammed Salman Alabbad; Naji Musa Alnuwaysir; Hussain Ali Bomuzah; Ayat Radhi Bumozah; Sarah Ali Abdullah Alkhalaf; Eman Hussin Saleh Almutair; et al. (International Journal of Scientific Research and Innovative Studies, 2022)
Rehabilitation in the Intensive Care Unit (ICU) plays a vital role in the holistic care of critically ill patients, aiming to mitigate the physical, cognitive, and psychological sequelae of critical illness. This review provides a comprehensive overview of the importance of rehabilitation in the ICU setting, including early mobilization and multidisciplinary rehabilitation interventions. We discuss the benefits of early mobilization, evidence supporting rehabilitation in the ICU, challenges and considerations in implementation, and future directions for research and practice. By highlighting the significant role of rehabilitation in optimizing patient outcomes and enhancing recovery, this review aims to promote the integration of rehabilitation practices into routine ICU care.